2018
DOI: 10.15252/embj.201798250
|View full text |Cite
|
Sign up to set email alerts
|

TFEB controls vascular development by regulating the proliferation of endothelial cells

Abstract: Transcription factor TFEB is thought to control cellular functions—including in the vascular bed—primarily via regulation of lysosomal biogenesis and autophagic flux. Here, we report that TFEB also orchestrates a non‐canonical program that controls the cell cycle/VEGFR2 pathway in the developing vasculature. In endothelial cells, TFEB depletion halts proliferation at the G1‐S transition by inhibiting the CDK4/Rb pathway. TFEB‐deficient cells attempt to compensate for this limitation by increasing VEGFR2 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 80 publications
(155 reference statements)
6
94
0
Order By: Relevance
“…Liver showed the strongest age correlation (cor=0.59) and both liver and blood exhibited the highest values from DNAmRep. This may reflect the higher proliferative capacity of cells in these samples [47,48]. Muscle also showed higher DNAmRep overall, but did not significantly increase with age.…”
Section: Discussionmentioning
confidence: 80%
“…Liver showed the strongest age correlation (cor=0.59) and both liver and blood exhibited the highest values from DNAmRep. This may reflect the higher proliferative capacity of cells in these samples [47,48]. Muscle also showed higher DNAmRep overall, but did not significantly increase with age.…”
Section: Discussionmentioning
confidence: 80%
“…Then, we found that one of the major regulators of p21, the tumor suppressor p53 [16,27,28,[42][43][44], is required for TFEB-mediated elevation of p21. Interestingly, a residual but significant activation of p21 was observed upon the overexpression of TFEB in p53 depleted background.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, TFE3 and TFEB contribute to sustaining p53-dependent response by stabilizing p53 protein levels [26]. Furthermore, TFEB depletion halts proliferation at the G1-S transition by inhibiting the CDK4/Rb pathway [27].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor EB (TFEB) is a master regulator of autophagy and lysosomal biogenesis. TFEB promotes endothelial cell proliferation by activating the autophagic flux and regulating the G1-S transition, which is conducive to angiogenesis [141,142]. In addition, the metabolites of autophagic lysosomes can be recycled into amino acids and lipids to produce adenosine triphosphate [143], which is also one of the mechanisms of endothelial cell proliferation mentioned above.…”
Section: Inducing Autophagymentioning
confidence: 99%